Suppressing of Irreversible Capacity in Lithium-ion Batteries - Libich,Jiri (2013)
The article deals with preparing of lithiated graphite material. The lithiated graphite material can be used as active electrode material in lithium-ion batteries. Most of the commercially produced lithium-ion batteries have the negative electrode based on graphite. The capacity losses which are caused by irreversible capacity of graphite may reduce the potential capacity of the battery from 15 % up to 45 %. These losses arise on negative electrode interphase (solid graphite electrode and liquid electrolyte), where during the formation process is created the SEI (Solid-Electrolyte Interphase) layer. The layer is composed from lithium atoms and the decomposition products of electrolyte solvents. The SEI layer is indispensable for correct function of lithium-ion battery. In this article are presented experimental methods for synthesis of lithiated graphite material. The article describes the three concepts of preparing lithiated material and its using like a precursor for preparing of negative electrode. The first method is based on using n-butyllithium (C4H9Li) reagent, its behaviour as the donor of lithium atoms, and graphite acts as the acceptor of lithium atoms. The second concept follows the first one only with adding an ionic compound to graphite, in our case FeCl3. The last concept presents the electroless lithiation process, which is based on different electrochemical potential between lithium and graphite.